(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
the study studies methods and approaches aimed at developing mobility in primary school students, as well as analyzing the impact of various types of exercise and physical activity on their physical and mental development. Particular attention is paid not only to the physical development of children, but also to the formation of their social skills, incentives to play sports and methods of play that contribute to the common interest in physical activity.